Presenting a model for evaluating the performance of financial accelerators of companies accepted on the Iranian Stock - Moradpour, Mojtaba (2021)
Financial accelerators and optimizing their performance have always been one of the most important issues in organizations and companies. This mixed (qualitative-quantitative) research was conducted with the aim of providing a model for evaluating the performance of financial accelerators for companies accepted on the Iranian Stock Exchange. This study was conducted using a mixed method (qualitative-quantitative) in which 21 variables of the model were extracted in the qualitative section and interviews were conducted with 19 experts and determining the relationship between variables to achieve the model in the quantitative part based on interpretive structural modeling (ISM).Qualitative and quantitative data analysis was the achievement of a five-level model that the most influential variables of this model in the fifth level of company Prosperity and recession and asymmetric information and the variables of market constraints, financial cost situation, financing mechanism, financial performance forecast, Short-term interest rates, financial friction, changes in net valuable, insurance costs and credit channels in the first level of this model were the most influential variables of this model, other variables are also connective variables.Serious attention to the period and level of prosperity and recession of companies and if possible the use of appropriate financial methods to predict the period of prosperity and recession can significantly improve the performance of financial accelerators. Also, due to the high effect of asymmetric financial information, the quality and timeliness of this information also affects the performance of financial accelerators.